- #1

- 141

- 0

4x - 1/3 - 2x + 7/6 = 5/2

I have worked it out as follows:

6(4x - 1) -3 (2x + 7) = 30/2

(here i have multiplied the right side by 6 as this is the LCM of 6 + 3.

24x - 6 - 6x - 21 = 15

18x - 27 = 15

18x = 42

x = 2.3333

^{r}

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- Thread starter Gringo123
- Start date

- #1

- 141

- 0

4x - 1/3 - 2x + 7/6 = 5/2

I have worked it out as follows:

6(4x - 1) -3 (2x + 7) = 30/2

(here i have multiplied the right side by 6 as this is the LCM of 6 + 3.

24x - 6 - 6x - 21 = 15

18x - 27 = 15

18x = 42

x = 2.3333

- #2

Mark44

Mentor

- 34,884

- 6,624

From the work you show later, your original equation is not written correctly. Apparently this is what you have.Have I solved this equation correctly? I don't think I have as I can't imagine the value of x being a recurring number.

4x - 1/3 - 2x + 7/6 = 5/2

[tex]\frac{4x - 1}{3} - \frac{2x + 7}{3} = \frac{5}{2}[/tex]

The way anyone who is at least halfway knowledgeable in mathematics would interpret your equation is this:

[tex]4x - \frac{1}{3} - 2x + \frac{7}{6} = \frac{5}{2}[/tex]

If the first equation is what you meant and you don't know how to write it using LaTeX, use parentheses, like so:

(4x - 1)/3 - (2x + 7)/6 = 5/2

I have worked it out as follows:

6(4x - 1) -3 (2x + 7) = 30/2

(here i have multiplied the right side by 6 as this is the LCM of 6 + 3.

24x - 6 - 6x - 21 = 15

18x - 27 = 15

18x = 42

x = 2.3333^{r}

Share: